Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ \(\left(x^4+\frac{1}{x^4}\right)\left(x^3+\frac{1}{x^3}\right)-\left(x+\frac{1}{x}\right)\)
\(=x^7+x+\frac{1}{x}+\frac{1}{x^7}-\left(x+\frac{1}{x}\right)=x^7+\frac{1}{x^7}\)
b/ Ta có:
\(\left(x+\frac{1}{x}\right)^2=49\)
\(\Leftrightarrow x^2+\frac{1}{x^2}=49-2=47\)
\(\left(x+\frac{1}{x}\right)^3=343\)
\(\Leftrightarrow x^3+\frac{1}{x^3}+3\left(x+\frac{1}{x}\right)=343\)
\(\Leftrightarrow x^3+\frac{1}{x^3}=343-3.7=322\)
\(\Rightarrow\left(x^2+\frac{1}{x^2}\right)\left(x^3+\frac{1}{x^3}\right)=47.322=15134\)
\(\Leftrightarrow x^5+\frac{1}{x}+x+\frac{1}{x^5}=15134\)
\(\Leftrightarrow x^5+\frac{1}{x^5}=15134-7=15127\)
a)\(\left(x^4+\frac{1}{x^4}\right)\left(x^3+\frac{1}{x^3}\right)-\left(x+\frac{1}{x}\right)=x^7+x+\frac{1}{x}+\frac{1}{x^7}-x-\frac{1}{x}\)
=\(x^7+\frac{1}{x^7}\)
\(x+\frac{1}{x}=7\)
=>\(x\left(x+\frac{1}{x}\right)=7x\)
=>\(^{x^2-7x+1=0}\)
=>\(x=\frac{7+3\sqrt{5}}{2};x=\frac{7-3\sqrt{5}}{2}loại\)
=>\(x^5+\frac{1}{x^5}=15127\)
a) \(49x^2-56x+16\)
\(=\left(7x-4\right)^2\)
\(=\left(7.2-4\right)^2=100\)
b) mk chỉnh lại đề
\(27x^3+54x^2+36x+8\)
\(=\left(3x+2\right)^3\)
\(=\left[3.\left(-2\right)+2\right]^3=-64\)
c) \(\left(x-1\right)^3-4x\left(x+1\right)\left(x-1\right)+3\left(x+1\right)\left(x^2+x+1\right)+3\left(x-1\right)^2\)
\(=6x^2+7x+5\)
\(=6.\left(-\frac{2}{5}\right)^2+7.\left(-\frac{2}{5}\right)+5\)
\(=\frac{79}{25}\)
Bài 1 : \(x^2+2x+1-y^2=\left(x+1\right)^2-y^2=\left(x+1-y\right)\left(x+1+y\right)\)
Bài 2 : \(10123^2-123^2=\left(10123-123\right)\left(10123+123\right)\)
\(=10000.10246=102460000\)
Bài 3 : \(x^2-18x=81\Leftrightarrow x^2-18x-81=0\)
\(\Leftrightarrow\left(x-9\right)^2-162=0\Leftrightarrow x=\frac{18\pm8\sqrt{2}}{2}=9\pm9\sqrt{2}\)
Trả lời:
1, \(\left(x-2\right)^3-\left(x+1\right)\left(x^2-x+1\right)+6\left(x-1\right)^2\)
\(=x^3-6x^2+12x-8-\left(x^3+1\right)+6\left(x^2-2x+1\right)\)
\(=x^3-6x^2+12x-8-x^3-1+6x^2-12x+6\)
\(=-2\)
2, \(-x\left(x+2\right)^2+\left(2x+1\right)^2+\left(x+3\right)\left(x^2-3x+9\right)-1\)
\(=\)\(-x\left(x^2+4x+4\right)+4x^2+4x+1+x^3+27-1\)
\(=-x^3-4x^2-4x+4x^2+4x+1+x^3+27-1\)
\(=27\)
(x - 1 ) ( x + 1 ) + 1
= (x + 1 )x - ( x + 1 ) + 1
= x2 + x - x - 1 + 1
= x2 + ( x - x ) + ( -1 + 1 )
= x2
(x - 1 ) (x + 1 ) + 1 = 0 nhe !